Effects of weaning age on pig performance in three-site production - Main, R.G.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two trials (n = 5,728 weaned pigs) were conducted to determine the effects of weaning age (12 to 21.5 days) on pig performance in a three-site production system. The second trial also examined the effects of modifying nursery feed budgets according to weaning age. In both studies, wean-to-finish ADG, mortality rate, average pig gain per days postweaning, and pounds sold per pig weaned improved linearly as weaning age increased. The improvements in growth rate and mortality largely occurred in the initial 42- days post-weaning, with some ongoing growth improvement to slaughter. Modifying nursery feed budgets did not affect wean-to-finish growth performance. These studies indicate increasing weaning age up to 21.5 days predictably improves grow-finish throughput within a three-site production system.
Keywords: Weaning age; Throughput; Growth; Swine